Movement Behaviors and Bone Biomarkers in Young Pediatric Cancer Survivors: A Cross-Sectional Analysis of the iBoneFIT Project - Gil-Cosano, Jose J.; Ubago-Guisado, Esther; Llorente-Cantarero, Francisco J.; Marmol-Perez, Andres; Rodriguez-Solana, Andrea; Pascual-Gazquez, Juan F.; Mateos, Maria E.; Molina-Hurtado, Jose R.; Garcia-Fontana, Beatriz; Narciso, Pedro Henrique [UNESP]; Klentrou, Panagiota; Gracia-Marco, Luis (MDPI, 2024)
Background/Objectives: This study aims to investigate the association of movement behaviors with irisin, sclerostin, and bone turnover markers in young pediatric cancer survivors. Methods: A total of 116 young pediatric cancer survivors (12.1 ± 3.3 years; 42% female) were recruited. Time spent in movement behaviors over at least seven consecutive 24 h periods was measured by accelerometers (wGT3x-BT accelerometer, ActiGraph). Blood samples were collected at rest and serum was analyzed for irisin, sclerostin, cross-linked telopeptide of type I collagen (CTX), procollagen type I amino-terminal propeptide (P1NP), total osteocalcin (OC), alkaline phosphatase (ALP), 25-hydroxyvitamin D, parathyroid hormone (PTH), calcium, phosphorous, and magnesium. Results: Irisin and sclerostin were not significantly correlated with bone turnover markers. Sedentary time was negatively correlated with the P1NP (r = −0.411, p = 0.027) and total OC (r = −0.479, p = 0.015) Z-scores, whereas moderate-to-vigorous physical activity was positively correlated with the P1NP (r = 0.418, p = 0.024) and total OC (r = 0.478, p = 0.016) Z-scores. Moreover, total physical activity was positively correlated with the total OC Z-score (r = 0.448, p = 0.025). Finally, the uncoupling index [CTX/P1NP] was positively correlated with sedentary time (r = 0.424, p = 0.012) and negatively correlated with light physical activity (r = −0.352, 0.041). Conclusions: Reducing sedentary time and increasing physical activity may favor bone formation over resorption in young pediatric cancer survivors.
Keywords: bone turnover; cancer; children; exercise; myokines; osteokines